Analysis of Social Media in Enhancing the Popularity and Reliability of Financial Statements Based on SAK EMKM - Trinanda, Muhammad; Nurbaiti, Nurbaiti; Nasution, Yenni Samri Juliati (LP2M IAIN Palopo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to national economies, yet they face challenges with reliable financial reporting and low adoption of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Digital technology, especially social media, offers opportunities to enhance business visibility and financial transparency. This study analyzes social media's role in improving MSME popularity and financial statement reliability based on SAK EMKM. Using a descriptive qualitative approach, this study conducts a case study of MSME